Obraz wroga w antyunijnym dyskursie na łamach czasopisma „Szczerbiec” - Forecki, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The Author analyzes the contents of the Szczerbiec periodical. It is an extremist right-wing, or even neo-Fascist, periodical rightfully present on the Polish editorial market next to other press titles. Its circulation is not high which may signify that the number of its readers tends to be limited and the bond between the sender and recipient is marginal. Although the periodical aims at a determined and devoted group of readers, it is available from common sales outlets. Therefore it is not an incriminated periodical that would provide its readers with the impression of tasting a forbidden fruit.